Human Fibroblast Gene Expression Modulation Using 940 NM Diode Laser - Illescas-Montes, Rebeca (Sci Rep, 2019)
Low-Level Laser Therapy is used as regenerative therapy in different clinical fields. This is due to its photobiomodulation effect via cell signaling on different cell populations, Including fibroblasts, cells involved in tissue regeneration and healing. The aim was to analyze the effect of 940 nm diode laser on the gene expression of different markers involved in fibroblast growth, differentiation, and migration. Real-time polymerase chain reaction (q-RT-PCR) was used to quantify the expression of fibroblast growth factor (FGF), connective tissue growth factor (CTGF), vascular-endothelial growth factor (VEGF), transforming growth factor β1 (TGF-β1), TGFβ-receptors (TGFβR1, TGFβR2, and TGFβR3), discoidin-domain receptor-2 (DDR2), matrix metalloproteinase-2 (MMP2), α-actin, fibronectin, decorin, and elastin on human fibroblast, treated with single dose (T1) or two doses (T2) of diode laser at 0.5 Watts and 4 J/cm(2). A significant increase in the expression of FGF, TGF-β1, TGFβR1, TGFβR2, α-actin, fibronectin, decorin, DDR2 and MMP2 was observed after both treatments. A decrease was observed in expression of elastin (T1 and T2), and CTGF (T2). These changes underlie the biostimulatory effect of laser on fibroblasts, which translates into an increase in short-term proliferation and in long-term differentiation to myofibroblasts. These data support the therapeutic potential of diode laser for wound repair.